The petroleum ether extract of Brassica rapa L. induces apoptosis of lung adenocarcinoma cells via the mitochondria-dependent pathway. Issue 20 (13th September 2021) - Halike, Xierenguli; Li, Jinyu; Yuan, Pengfei; Yasheng, Kaimeiliya; Chen, Min; Xia, Lijie; Li, Jinyao
Abstract : BRPS inhibited the growth of lung cancer cells through inducing cell cycle arrest, mitochondria-dependent apoptosis, and activating immunity of mice. Abstract : Brassica rapa L. is one of the most popular traditional foods with a variety of biological activities. In this study, the petroleum ether extract of B. rapa was separated by silica gel column chromatography, and named BRPS, which was identified by LC-MS. The effects and pharmacological mechanisms of BRPS on the treatment of lung cancer were investigated both in vitro and in vivo . The results showed that BRPS significantly inhibited the proliferation of both human lung cancer A549 and mouse lung cancer LLC cells, while its toxicity to normal cells was lower than that of cancer cells. BRPS induced cell cycle arrest at the G2/M phase and significantly reduced the levels of CDK1 and CyclinB1 in A549 cells. Moreover, BRPS induced apoptosis in a dose-dependent manner, and increased the Bax/Bcl-2 ratio, while it decreased mitochondrial membrane potential, promoted the release of cytochrome c, activated caspase 9 and 3, and enhanced the degradation of PARP in A549 cells. Furthermore, the levels of reactive oxygen species (ROS) were also upregulated by BRPS and ROS inhibitor reversed BRPS-induced apoptosis. Importantly, BRPS significantly suppressed the growth of LLC cells in vivo without any obvious side effect on body weight and organs of mice, and increased the proportion of B cells, CD4 + T cells, CD8 + T cells and CD44 + CD8 + T cells in the spleen. These results revealed that BRPS inhibited the growth of lung cancer cells through inducing cell cycle arrest, mitochondria-dependent apoptosis, and activating immunity of mice, and BRPS might be a potential anti-tumor functional food and promising agent for the treatment of lung cancer.